(untitled) (Bangladesh Journal of Microbiology, 2008)
In the present investigation a total 630 black tiger and brown ready-to-cook/eat shrimp samples collected from a fish processing industry was analyzed. Total aerobic plate count (APC) was found to exceed the International Commission on Microbiological Specification for Foods (ICMSF) standard in case of 2.26% black tiger shrimp and 1.86% brown shrimp samples. Escherichia coli counts of all the samples were within the acceptable limit of ICMSF standard. However, considering the Council of the European Communities (EEC) standard, coliform (E. coli) counts of 0.96% black tiger and 0.62% brown shrimp samples exceeded the acceptable limit. Coagulase-positive Staphylococcus aureus, Salmonella and Listeria monocytogenes were not detected from any specimens. The fish processing seems to follow the hazard analysis and critical control point (HACCP) principles that should be more strictly maintained in order to keep the quality of shrimp of international standard. Keywords: Ready-to-cook/eat shrimps, Bacteriological count, Hazard analysis and critical control point (HACCP) DOI: http://dx.doi.org/10.3329/bjm.v24i2.1247 Bangladesh J Microbiol, Volume 24, Number 2, December 2007, pp 81-84